The history of food exchanges: a new agenda - Atkins, Peter (Food & History, 2009)
Abstract This paper argues that the time has come for a new approach to food exchange. Using the literatures of geography and sociology, it points out that the social constructionism that is being used increasingly in food studies is inadequate. Its privileging of human agency has led to an underestimation of the importance of the materiality of foodstuffs. Three dimensions are proposed for a rematerialisation of research on food exchange histories.